The Quartz Conundrum : understanding the role of quartz in the composition of late Pleistocene and Holocene lithic assemblages from the Verlorenvlei area, Western Cape - Orton, Jayson (Department of Archaeology, 2014)
Includes bibliographical references (leaves 283-303).